Teacher Workload and Leadership Support in Technology-Integrated Educational Management: A Systematic Literature Review - Fauzi, Rizal; Laia, Risman; Alrasyid, Farid Datu; Sugiharti, Rafika Nur; Wanma, Paulina Paniai Anyke; Pratiwi, Ika (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
Excessive workload imposed on teachers poses a significant threat to their mental health, leading to emotional exhaustion and a decline in psychological well-being. This phenomenon has the potential to trigger burnout (chronic work fatigue) that destructively impacts educational performance. This article aims to systematically review recent literature on the dynamics of the relationship between job demands and leadership support (job resources) on teacher burnout and performance levels. This study uses a Systematic Literature Review (SLR) method by examining 12 reputable journal articles (national and international) from the 2021–2024 period. Data analysis was conducted through data reduction, data presentation, and drawing conclusions based on the Job Demands-Resources (JD-R) theoretical framework. The findings consistently show that excessive workload has a strong positive correlation with work stress and a decline in professionalism. However, these negative impacts can be significantly mitigated by certain leadership styles. Servant Leadership and Spiritual Leadership have been proven effective as moderating variables that enhance Quality of Work Life (QWL), job satisfaction, and organizational commitment, which in turn suppress turnover intention. Conclusion: Modern educational management must shift from a purely instructional approach to a humanistic approach that balances workload ratios with psychological support from leaders.